(untitled) (Research, Society and Development, 2023)
Objective: to identify the partner’s participation in prenatal care. Method: integrative literature review conducted in electronic databases MEDLINE via Pubmed, SCOPUS, CINAHL and LILACS, in the period from 2010 to 2020. The included studies were submitted to content analysis. Results: 22 studies published in the period from 2010 to 2019 were included. Data were analyzed according to five thematic categories: 1) Partner’s experiences in prenatal care and the overview of participation, 2) Facilitators and barriers to partner’s participation in prenatal care, 3) Pregnant women’s views on partner’s participation in prenatal care, and 4) Nurses’ challenges to the effectiveness of partner’s participation in prenatal care. Conclusion: Partner participation was low and associated with both positive and negative experiences. This highlights the importance of training nurses for an integral, inclusive, and respectful care, which includes the partner in the care plan.